2012
DOI: 10.5586/aa.2010.008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water Stress on the Gas Exchange Parameters, Productivity and Seed Health of Buckwheat (Fagopyrum esculentum Moench)

Abstract: The present pot experiment studied the effect of different soil moisture contents (60 - 70% CWC (capillary water capacity) - control; 30 - 35% CWC - water stress) on buckwheat productivity, the gas exchange parameters and health of buckwheat nuts. It was found that water deficit affected adversely certain biometric features investigated (plant height, number of nuts per cluster) and caused a decrease in seed weight per plant. It was also shown that water stress reduced the values of the investigated gas exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In response to drought, F. esculentum showed a reduction in the stomatal conductance and the transpiration rate in our study. This decrease in stomatal conductance translates a closure of the stomata, which is the first response to drought in many species (Schapendonk et al, 1989;Arnau et al, 1997;Delpérée et al, 2003;Nakayama et al, 2007;Tadina et al, 2007;Pszczółkowska et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to drought, F. esculentum showed a reduction in the stomatal conductance and the transpiration rate in our study. This decrease in stomatal conductance translates a closure of the stomata, which is the first response to drought in many species (Schapendonk et al, 1989;Arnau et al, 1997;Delpérée et al, 2003;Nakayama et al, 2007;Tadina et al, 2007;Pszczółkowska et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In response to drought, F. esculentum showed a reduction in the stomatal conductance and the transpiration rate in our study. This decrease in stomatal conductance translates a closure of the stomata, which is the first response to drought in many species (Schapendonk et al, 1989; Arnau et al, 1997; Delpérée et al, 2003; Nakayama et al, 2007; Tadina et al, 2007; Pszczółkowska et al, 2012). Indeed, this change allowed a reduction in transpiration which results in less water loss and the maintenance of the water status (Schapendonk et al, 1989; Cornic and Massacci, 1996; Nakayama et al, 2007), as observed in F. esculentum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severe water stress directly affects photosynthetic capacity of the mesophyll causing decrease in carboxylation as well as electron transport chain activities, and/or induces ultrastructural changes in chloroplasts [71]. A decrease in the rates of photosynthesis and transpiration as well as in intercellular-space CO2 concentration and stomatal conductance was shown under water deficit conditions relative to the control [72]. Water stress results in stomatal closure and reduced transpiration rates, a decrease in the water potential of plant tissues, decrease in photosynthesis and growth inhibition [73].…”
Section: Effect Of Water Stress On the Physiological Components Of Wheatmentioning
confidence: 97%